A SEMANTIC ANALYSIS OF MUBHAM AL-DALALAH: ITS IMPLICATIONS FOR THE INTERPRETATION OF RELIGIOUS TEXTS - Armalena, Armalena; Amran, Ali; Erman, Erman; Ardianto, Firdaus; M, Mukhlis; Ritonga, Mahyudin; Rusydi, Rusydi (Referensi Islamika: Jurnal Studi Islam, 2026)
This research investigates the semantic complexities of Mubham al-Dalalah to determine its influence on the interpretative process of religious scriptures. It aims to explain how textual ambiguity functions within Islamic legal interpretation and contributes to maintaining legal flexibility across different temporal and social contexts. The study employs a qualitative library research methodology grounded in semantic-hermeneutic principles. Classical Usul al-Fiqh literature is integrated with modern linguistic theories, with classical treatises serving as the primary data source for analyzing four levels of semantic ambiguity. The findings classify semantic ambiguity into four categories: Khafi, Mushkil, Mujmal, and Mutashabih, each requiring a distinct level of interpretative rigor. The study demonstrates that semantic analysis transforms ambiguity from a linguistic obstacle into an opportunity for ijtihad, while contextual considerations are essential for selecting appropriate meanings consistent with divine intent and justice. Furthermore, integrating classical Islamic scholarship with contemporary linguistic approaches produces a more comprehensive understanding of religious texts. The study provides a theoretical framework for strengthening contemporary Islamic legal interpretation by combining classical Usul al-Fiqh with modern semantic analysis. It offers guidance for scholars and jurists in addressing contemporary legal and social issues while preserving fidelity to Islamic textual principles, thereby enhancing the relevance of religious interpretation in increasingly pluralistic and globalized societies. The originality of this study lies in its integration of classical Islamic semantic theory (Mubham al-Dalalah) with modern linguistic and hermeneutic approaches. By systematically conceptualizing the four hierarchical levels of semantic ambiguity within a contemporary interpretative framework, the research provides a novel analytical model that bridges traditional Islamic jurisprudence and modern linguistic scholarship.